2023
DOI: 10.1128/spectrum.04052-22
|View full text |Cite
|
Sign up to set email alerts
|

Flufenamic Acid, a Promising Agent for the Sensitization of Colistin-Resistant Gram-Negative Bacteria to Colistin

Abstract: Colistin is a last-line antibiotic used for the treatment of MDR Gram-negative bacterial infections. However, increasing resistance to it has been observed during clinical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…We found that both DS and flufenac acid had a diphenylamine structure, and the combined effect of flufenac acid and colistin had been previously confirmed. 28 We suspect that this structure may play a role, which our team is currently investigating. Considering the future application, we have concerns regarding the antibacterial efficacy of DS in the human body.…”
Section: ■ Discussionmentioning
confidence: 97%
“…We found that both DS and flufenac acid had a diphenylamine structure, and the combined effect of flufenac acid and colistin had been previously confirmed. 28 We suspect that this structure may play a role, which our team is currently investigating. Considering the future application, we have concerns regarding the antibacterial efficacy of DS in the human body.…”
Section: ■ Discussionmentioning
confidence: 97%
“…The cytotoxicity of Vero cells was detected by cell counting kit-8 (CCK-8) assay (Solarbio life sciences) based on previous report ( Zhang et al, 2023 ). The cells were plated in a 96-well plate at a density of 3 × 10 4 cells per well and treated with colistin (0.5, 1, 2, 4, 16, 32, 64 and 16 μg/mL) or the combination of colistin (0.5, 1, 2, 4, 16, 32, 64 and 16 μg/mL) and oxethazaine (20 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…We based our methodology on previous reports, with minor modifications ( 24 ). Four COL-R A. baumannii and four COL-R E. coli isolates were randomly selected to evaluate the eradication effect of NTZ combined with COL on mature biofilms.…”
Section: Methodsmentioning
confidence: 99%